Negative Politeness Strategies Used by American Girl in TV Series Emily in Paris - Riszha Nurlayli; Widyastuti Widyastuti (J-Lalite: Journal of English Studies, 2022)
The objective of this study is to identify and describe the negative politeness strategies across cultures. The use of politeness strategies will differ depending on the context and the factors that influence it. With regard to that, the TV series Emily in Paris was chosen for this study in which Emily Cooper, the main character, played the young American girl who is hired by a marketing company in Paris. This study applies the theory of politeness proposed by Brown and Levinson (1987) and the supporting theory by Holmes and Wilson (2017) about social factors that can affect politeness. This research is descriptive qualitative research. The data were taken from Emily Cooper’s utterances in the form of words, or phrases. The results of this study exposed that there are five kinds of negative politeness strategies found in Emily's utterances: giving deference, apologizing, questioning, or hedging, stating the FTA as a general rule and being conventionally indirect. At the same time, the social factors that influence Emily in using politeness are the participant, the setting, the topic, and the function. In addition, apologizing became the most strategy used by Emily because she tried to be polite and avoid any offense to her interlocutors.